BALI INTERNATIONAL SCHOOL OF ARTS (BISA) For International Students & Artists Coming to Bali: BALI INTERNATIONAL SCHOOL OF ARTS (BISA) For International Students & Artists Coming to Bali - Sedana I Nyoman (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
To complement MBKM (Freedom Campus-Freedom to Learn) featuring threesemester off-campus internship program, we are keen to establish Bali International School of Arts (BISA) for international students coming to Bali. i While MBKM policy renewing educational system by realizing on multiple partnership, BISA is committed to serve as the epicenter of the academic artistic collaboration. In doing so BISA provides creative space to welcome international students, artists, scholars, and cultural visitors to network and to develop stronger performance position with exhibition outcomes, ensuring the preservation of cultural expression while encouraging contemporary extensions. Just as MBKM, BISA cherishes partnership based on equal-global-relation in seeking better ways of doing things through industrial partnership and free enterprise. Adopting English as the primary way of communication BISA also opens her doors for enriching students’ knowledge, skills, and preworking experiences beyond its area of specialty, capable of seizing future opportunities through necessary creativity and innovation. To guaranty our service to international students (including visiting artists scholars who may be interested in experiencing fantastic cultural art uniquely Bali) we are cooperating to merge our current Balimodule (https://www.balimodule.com/) with the best art companies in several regions of the island. Adapting such method of co-operation BISA will invest four hallmarks from Badung to Karangasem regency: (1) Contemporary / Environmental Dance directed by Dr. Agung Rahma; (2) Traditional and Contemporary Topeng Mask & Wayang Puppetry directed by Made Sidia; (3) Traditional Dance and Gamelan Music directed by Agung Anom; and (4) Folk Arts and its Ethnology, directed by Dr. Catrini Pratihari. Balimodule as the main trunk should keep on nurturing such four branches, while enjoying better capacity to serve her local and international students.